IDENTIFIKASI SECARA MORFOLOGI DAN MORFOMETRI NEMATODA ENTOMOPATOGEN PADA LAHAN PERTANAMAN JAGUNG DI KABUPATEN GUNUNGKIDUL - Kholilurrahman Fathani, Kholil; Ajri, Miftahul (Jurnal Agrivet, 2025)
Corn productivity often declines due topest attacks, but can be controlled through the use of biological agents such asentomopathogenic nematodes (EPN). This study aims to explore andidentify EPN in corn fields in Gunungkidul Regency morphologically and morphometrically. Soil samples were taken in five districts, namely Wonosari, Playen, Patuk, Karangmojo, and Semanu. NEP trapping was carried out using Tenebrio molitor larvae, then isolatedusing the white head tray method and observed morphologically and morphometrically using a microscope. The results showed that the highest NEP population NEP population was found in Playen Subdistrict (462.67 NEP/5 ml) and the lowest in Patuk Subdistrict (7.33 NEP/5 ml). Population variation is thought to be influenced by differences in soil texture and cultivation systems. Based on the morphological and morphometric characteristics of the NEP found in Gunungkidul corn fields, they were identifiedas Heterorhabditis indica, with a body length ranging from 438.77–501.9 µm. These findings indicate the potential of H. indica as a biological agentin pest control in corn farming ecosystems in the Gunungkidul. Keywords : morphology, morphometry, population, Tenebrio molitor, white head tray